Standard forms of construction contracts in Romania - Cristian Bănică (Urbanism. Arhitectura. Constructii, 2013)
Construction industry in Romania is under pressure to modernize in order to cope with the new demands of development and convergence with EU. Contractual procedures in construction have to become an integral part in this process of modernization. The article makes an introduction to the advantages of standard forms of contract and professional contract administration in construction and presents the current state-of-the art in the use of standard construction contracts in Romania. Some practical conclusions and recommendations are presented considering the need for further contract studies.